Evaluation of titanium mesh cranioplasty and polyetheretherketone cranioplasty: protocol for a multicentre, assessor-blinded, randomised controlled trial (BMJ Open)
Introduction Cranioplasty is a common surgery in neurosurgery department. However, restoring the integrity of skull brings many challenges to surgeons, and the selection of ideal implant materials is throughout the history of cranioplasty. Although titanium mesh was still preferred by many neurosurgeons in cranial reconstruction, the new polyetheretherketone (PEEK) material, for example, is gaining popularity for craniofacial reconstruction today. There remain limited data that compare the outcome of PEEK cranioplasty and titanium mesh cranioplasty. It is necessary to conduct a study to compare outcome of different materials for cranioplasty.Methods/design In this multicentre, assessor-blinded, randomised controlled study, we will randomise 140 patients in a 1:1 ratio to PEEK cranioplasty versus titanium cranioplasty. Eligible patients are adults who were diagnosed with cranial defect (due to severe traumatic brain injury, ischaemic stroke, haemorrhagic stroke, infiltrative tumour and so on), the defect size is over 25 cm2, and they need to agree to participate in this trial. Instead of standard examinations, the enrolled patients receive neurological, motor, cognitive function and cerebral hemodynamics examinations as well as cosmetic evaluation. The procedures are repeated 3, 6 months after cranioplasty. The primary outcome, defined as infection or implant exposure after surgery, is the implant failure rate within 6 months. Secondary outcomes include postoperative complication rates, neurological outcomes, motor function, cerebral hemodynamics, cosmetic outcome and the total cost over a 6-month period.Ethics and dissemination This trial protocol has been approved by Biomedical Research Ethics Committee of West China Hospital of Sichuan University. All patients will be fully informed the implant materials, potential complications after surgery, responsibilities during the trial, and they will sign the informed consent before joining in this trial. If the patient’s cognitive function is impaired, the patient’s next of kin would be carefully informed. The results will be disseminated through academic conferences, student theses and will be published in a peer-reviewed journal.Trail registration number ChiCTR1900024625; Pre-results.